Superelement reduction of substructures for sequential load calculations in OpenFAST. (January 2020) - Branlard, E.; Shields, M.; Anderson, B.; Damiani, R.; Wendt, F.; Jonkman, J.; Musial, W.; Foley, B.
Abstract: This article presents the superelement formulation newly implemented in OpenFAST to simulate fixed-bottom substructures with a reduced-order model similar to a common industry practice. The Guyan and Craig-Bampton methods are used to reduce the number of degrees of freedom and generate a so-called "superelement". The formulation allows manufacturers to exchange such superelements to perform load calculations without revealing sensitive information about the support structure (e.g., foundation, substructure, and/or tower) or turbine. The source code is made publicly available in the OpenFAST repository. Test cases with varying degrees of complexity are presented to validate the technique, and accuracy issues are discussed.